Strategi Pengembangan Kurikulum Merdeka dalam Mewujudkan Profil Pelajar Islami di SDIT Ar Rahman Sukoharjo - Annisa Rahmawati; Hanifa Farras; Ilmawati Ilmawati; Khonsa Mujahidah; Najda Syifa’un; Praptiningsih Praptiningsih (Mathematics Education Study Program, 2025)
This study aims to describe the development strategies of the Merdeka Curriculum in shaping the profile of Islamic learners at SDIT Ar Rahman Sukoharjo. Using a qualitative approach, data were collected through interviews with the principal and Islamic Education (PAI) teachers as the primary sources. The findings reveal that the school develops its curriculum by strengthening flagship programs such as tahfidz, integrating Islamic values into learning activities and daily school life, and implementing continuous character-based assessment. Differentiated strategies are applied to accommodate students’ varying abilities through personalized approaches, additional learning hours, and intensive communication with parents. Teachers play a central role as mentors and role models in cultivating students’ character, discipline, and learning independence. Evaluation is conducted both formatively and summatively, emphasizing academic performance and behavioral aspects. Furthermore, extracurricular activities such as tahfidz and scouting support the reinforcement of students’ Islamic character. The study concludes that the synergy among the principal, teachers, and parents is essential in developing an Islamic value oriented curriculum and fostering the profile of Islamic learners at SDIT Ar Rahman Sukoharjo.